P-E2 The Impact of structured mentor mother support on retention during the first 12 months postpartum among HIV positive women in rural Nigeria. (April 2018) - Fan-Osuala, Chinenye; Ramadhani, Habib; Erekaha, Salome; Anaba, Udochisom; Nwanne, Gift; Bathnna, Miriam; Charurat, Manhattan; Sam-Agudu, Nadia
Abstract : Introduction: With the advent of lifelong therapy, interventions that sustain long-term engagement with PMTCT services are needed. We evaluated the impact of a structured peer support program on postpartum PMTCT retention among rural Nigerian women. Methods: This prospective cohort study enrolled HIV+ pregnant women from 20 primary healthcare centers (PHCs). Ten PHCs with structured mentor mother (MM) support (training, supervision, client tracking, standard documentation and performance evaluation) were pair-matched with 10 routine unstructured peer support (PS) PHCs. Participants received viral load at 6 months and were followed up to 12 months postpartum. Viral suppression was defined as <20 copies/mL. Retention assessment was based on monthly and bi-monthly clinic visits in the first and second 6 month postpartum periods respectively. Participants with ≥5 of 9 expected visits were considered retained. A logistic regression model with generalized estimating equation was used to evaluate the effect of PS and other factors on retention. Results: Of 497 women enrolled, 260 and 237 were exposed to MM and routine PS respectively. Women with MM support (aOR = 6.6, 95% CI 3.4 to 13.1) and viral suppression at 6 months (aOR = 3.1, 95% CI 1.8 to 5.6) had higher odds of retention during the 12 month postpartum period. Age, distance from PHC, religion, gravidity, disclosure & time of diagnosis had no effect on retention. Discussion: Structure in peer support programs improved retention. Also, viral suppression had an independent effect on retention, indicating a strong link between adherence and sustained engagement; both being essential for PMTCT. Conclusion: Built-in structure can significantly enhance the impact of PS interventions on PMTCT outcomes.